2023
DOI: 10.3390/polym15204144
|View full text |Cite
|
Sign up to set email alerts
|

3D-Printed Filters for Efficient Heavy Metal Removal from Water Using PLA@CS/HAP Composites

Yisu Wang,
Yan Wang,
Shuai Qiu
et al.

Abstract: Chitosan/Hydroxyapatite composites, enriched with relatively active -NH2 and -OH groups, have emerged as promising adsorbents for heavy metal removal. In this study, we harnessed the potential of CS/HAP composites by developing monolithic PLA@CS/HAP filters utilizing 3D printing and freeze-drying techniques. These filters possess both macroscopic and microscopic porous structures, endowing them with exceptional capabilities for removing heavy metals from water. The adsorption properties of CS/HAP composites we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…A new work using a chitosan-hydroxyapatite coupled with PLA to create monolithic filters utilizing 3D printing demonstrated robust Cu 2+ removal performance with a maximum adsorption capacity of 119 mg/g, exhibiting the ability to remove more than 80% Cu 2+ from their sample in less than 35 min ( Wang et al, 2023b ). The graphical representation of how the authors fabricate the filter can be seen in Fig.…”
Section: Applications Of 3d Printing In Bioremediationmentioning
confidence: 99%
See 1 more Smart Citation
“…A new work using a chitosan-hydroxyapatite coupled with PLA to create monolithic filters utilizing 3D printing demonstrated robust Cu 2+ removal performance with a maximum adsorption capacity of 119 mg/g, exhibiting the ability to remove more than 80% Cu 2+ from their sample in less than 35 min ( Wang et al, 2023b ). The graphical representation of how the authors fabricate the filter can be seen in Fig.…”
Section: Applications Of 3d Printing In Bioremediationmentioning
confidence: 99%
“…The graphical representation of how the authors fabricate the filter can be seen in Fig. 5 (Reused with permission from ( Wang et al, 2023b )). A previous work where a reusable monolithic 3D porous adsorbing filter was 3D printed using chitosan for heavy metal removal showed an adsorption capacity of 13.7 mg/g with adsorption kinetics of 2.2 mg/m per minute for Cu 2+ removal and this is further proof for the role of 3D bioprinting in the field of bioremediation ( Zhang et al, 2019 ).…”
Section: Applications Of 3d Printing In Bioremediationmentioning
confidence: 99%
“…The study revealed that the adsorption process aligned with Freundlich and pseudo-second-order models, suggesting a multi-layer adsorption with chemisorption characteristics for the CS/HAP composite adsorbent. Cu 2+ reusability experiments demonstrated the resilience of PLA@CS/HAP filters, maintaining consistent Cu 2+ removal capacity over five consecutive adsorption–desorption cycles, with a significant removal efficiency of 97.17% [ 184 ].…”
Section: Applications Of Biopolymeric Nanocomposites In Wastewater Re...mentioning
confidence: 99%